Flower-like architecture of CoSn4 nano structure as anode in lithium ion batteries. (4th May 2017) - Javadian, Soheila; Kakemam, Jamal; Gharibi, Hussein; Kashani, Hamideh
Abstract: CoSn4 nano-particles were synthesized on Cu and Ni substrates through pulsed current electrodeposition and used as anode in lithium ion batteries. Nano particles with Flower-like morphology were obtained through applying an average current density of 85 mA/cm 2 on Ni substrate while the particles formed using constant current electrodeposition are greater in size ca. 500 nm. Optimum discharge capacity of synthesized CoSn4 was obtained 848 mAh g −1 which reduced to 500 mAh g −1 at 120th cycle indicating an enhanced electrochemical performance compared to anode films synthesized through other pulsed current densities and also constant current electrodeposition. This high discharge capacity and cycleability is attributed to finer crystal grains and flower-like morphology of nano particles. Also, the sample synthesized on Ni substrate showed higher cycleability and noticeably lower resistance. High resistance of anode film synthesized on Cu substrate is due to the corrosion and passivation of copper occurred by HF formation in LiPF6 electrolyte. Graphical abstract: Highlights: Pulsed Current parameters can control the electrodeposition kinetics. Anode morphology reflects its electrochemical performance in LIB's. Fine grained CoSn4 flower-like nanoparticles can have superior electrochemical performance. Ni has lower resistance regarding stability against HF corrosion in LiPF6 medium.